2018
DOI: 10.1136/bjsports-2018-099836
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prenatal exercise on neonatal and childhood outcomes: a systematic review and meta-analysis

Abstract: ObjectiveWe aimed to identify the relationship between maternal prenatal exercise and birth complications, and neonatal and childhood morphometric, metabolic and developmental outcomes.DesignSystematic review with random-effects meta-analysis and meta-regression.Data sourcesOnline databases were searched up to 6 January 2017.Study eligibility criteriaStudies of all designs were eligible (except case studies and reviews) if published in English, Spanish or French, and contained information on the relevant popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
153
2
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(179 citation statements)
references
References 150 publications
15
153
2
9
Order By: Relevance
“…23 A metaanalysis has reported that maternal exercise during pregnancy was safe and beneficial for fetus. 24 Moreover, maternal exercise was found associated with reduced odds of macrosomia and was not associated with neonatal complications as well as adverse childhood outcomes. 24 Another study highlighted that there were no significant differences in the low birth weight, fetal or neonatal death between physically active and non-active pregnant women.…”
Section: Discussion:-mentioning
confidence: 96%
See 1 more Smart Citation
“…23 A metaanalysis has reported that maternal exercise during pregnancy was safe and beneficial for fetus. 24 Moreover, maternal exercise was found associated with reduced odds of macrosomia and was not associated with neonatal complications as well as adverse childhood outcomes. 24 Another study highlighted that there were no significant differences in the low birth weight, fetal or neonatal death between physically active and non-active pregnant women.…”
Section: Discussion:-mentioning
confidence: 96%
“…24 Moreover, maternal exercise was found associated with reduced odds of macrosomia and was not associated with neonatal complications as well as adverse childhood outcomes. 24 Another study highlighted that there were no significant differences in the low birth weight, fetal or neonatal death between physically active and non-active pregnant women. 25 The reported evidence are similar to as identified in the current study where no significant difference was found in living status, admission to NICU, and vaginal non instrumental delivery between pregnant women who achieved recommended physical activity level and those who did no.…”
Section: Discussion:-mentioning
confidence: 96%
“…In addition, prenatal exercise is safe and beneficial for the fetus. The maternal exercise was associated with reduced odds of macrosomia (abnormally large babies) and was not associated with neonatal complications or adverse childhood outcomes (Davenport et al, 2018).…”
Section: The Difference In the Anxiety Levels Post-intervention Betwementioning
confidence: 90%
“…25,26 By contrast, buoyancy in water might release the gravity-induced compression and improve cardiac preload/output. 17 Conventional physical activities such as land walking might have some benefits, 1,6,10 whereas exercise on land may have potential risks to reduce renal perfusion and urinary volume through vasoconstriction. 17…”
Section: Discussionmentioning
confidence: 99%
“…However, advantages of behavioral interventions are also inconsistent, and currently, maternal physical activities during pregnancy are not a guideline recommendation. 1,6 For example, in recent systematic reviews, prenatal maternal exercise was safe, had benefits for the fetus, and was not associated with neonatal complications and adverse childhood outcomes, 10 whereas behavioral interventions (including the broad range of education, diet, exercise, and self-monitoring of blood glucose) did not prevent hypertensive disorders of pregnancy. 11 To improve guidelines in maternal physical activities during pregnancy, focusing “specific” physical activities in the biological pathogenesis of preeclampsia should be a priority.…”
Section: Introductionmentioning
confidence: 99%